2015
DOI: 10.1136/bjophthalmol-2015-307806
|View full text |Cite
|
Sign up to set email alerts
|

Phase IIb clinical trial of ranibizumab for the treatment of uveitic and idiopathic choroidal neovascular membranes

Abstract: . (2016). Phase IIb clinical trial of ranibizumab for the treatment of uveitic and idiopathic choroidal neovascular membranes. British Journal of Ophthalmology, 100(9), 1221 -1226 . DOI: 10.1136 /bjophthalmol-2015 Peer reviewed version Link to published version (if available): 10.1136/bjophthalmol-2015-307806 Link to publication record in Explore Bristol Research PDF-document This is the author accepted manuscript (AAM). The final published version (version of record) is available online via BMJ at http://b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous studies have reported promising results with anti-VEGF therapy in ICNV patients891042. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported promising results with anti-VEGF therapy in ICNV patients891042. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Despite some promising results with anti-VEGF agents in treating inflammatory CNV, the current data is limited by lack of comparative studies, and further data from prospective controlled studies are required to fully determine the role of anti-VEGF therapy for the inflammatory CNV. [13] Although, intravitreal anti-VEGF has been widely used for inflammatory CNVMs, there are only a few anecdotal reports in the context of CNVM secondary to infectious and particularly fungal chorioretinitis. Successful outcomes have been documented in CNVM related to ocular toxocariasis following three consecutive injections of ranibizumab.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, about 11% of the eyes (2/17) had “medusa-shaped” lesions, and the rate of this structure was lower than those in AMD patients [ 20 ]. Previous trials proved that ICNV was treated more effectively by anti-VEGF drugs than AMD, because the former needed fewer injections and gained better vision [ 6 , 21 ]. Although the size of the lesion and duration of disease were related to treatment effects, we speculate that different neovascular morphology, such as “tree-in-bud” in ICNV and other structures in AMD, will cause different outcomes and prognosis after anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because vascular endothelial growth factor (VEGF) is part of the pathophysiology of CNV [ 3 ], anti-VEGF therapy has become the first-line treatment for ICNV patients [ 4 ]. Intravitreal injection of bevacizumab and ranibizumab improves and stabilizes the vision of patient with ICNV [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation